2010
DOI: 10.1016/j.molcel.2010.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Nrf1 Mediates the Proteasome Recovery Pathway after Proteasome Inhibition in Mammalian Cells

Abstract: SUMMARY In Saccharomyces cerevisiae, chemical or genetic inhibition of proteasome activity induces new proteasome synthesis promoted by the transcription factor RPN4. This ensures that proteasome activity is matched to demand. This transcriptional feedback loop is conserved in mammals, but its molecular basis is not understood. Here we report that Nuclear factor erythroid derived 2-related factor 1 (Nrf1), a transcription factor of the cap ‘n’ collar basic leucine zipper family, but not the related Nrf2, is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
630
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(675 citation statements)
references
References 49 publications
41
630
2
2
Order By: Relevance
“…Aside from its role in constitutive expression of proteasome genes, we have also demonstrated that Nrf1 is required for inhibitor-induced proteasome gene expression (28). On the basis of these findings, we propose that Nrf1 is essential for expression of mammalian 26S proteasome under basal as well as stress-induced conditions.…”
Section: Discussionmentioning
confidence: 63%
“…Aside from its role in constitutive expression of proteasome genes, we have also demonstrated that Nrf1 is required for inhibitor-induced proteasome gene expression (28). On the basis of these findings, we propose that Nrf1 is essential for expression of mammalian 26S proteasome under basal as well as stress-induced conditions.…”
Section: Discussionmentioning
confidence: 63%
“…This mechanism might also function in concert with the previously demonstrated transcriptional regulation [52,53] to form a feedback loop regulating proteasome homeostasis ( Figure 5E), which could upregulate proteasome function and functionally compensate for BTZ-induced compromise in proteolytic capacity. This may collectively reduce BTZ cytotoxicity, thus providing an additional avenue for drug resistance in BTZ-treated cancer cells.…”
Section: Discussionmentioning
confidence: 63%
“…Proteasomal inhibition was found to activate Nrf1- [52] or Nrf2-mediated [53] transcription of some proteasome subunits, which gave rise to the so-called "proteasome bounce-back response". Overexpression of or mutations in PSMB5 gene were also reported in BTZ-resistant cancer cells [3,54,55].…”
Section: Btz Stabilized Proteasome Subunits Psmc1 and Proteasome Assementioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, this protective effect against apoptosis could be attributed to the Nrf2-induced expression of proteasomal genes leading to an elevated proteasome activity in tumor cells (11, 19 -24). Whereas this proteasome inducing effect of Nrf2 in response to oxidative and electrophilic stress has been widely reported already (11,(25)(26)(27)(28)(29)(30), recent data revealed that the closely related transcription factor Nrf1 (TCF11) plays a particular role in the maintenance of constitutive proteasome activity (31). Moreover, Nrf1 mediates the inducing effect of proteasome inhibitors on proteasomal gene expression to a greater extent than Nrf2 (31,32).…”
mentioning
confidence: 91%